Individual differences in the effects of Task-Shifted Psychotherapy for Depression: Study Protocol of An Individual Patient Data Meta-analysis - Ricardo Araya; Ronald C Kessler; Pim Cuijpers; Eirini Karyotaki; Vikram Patel; Yagmur Amanvermez (OSF Registries, 2020)
More than 320 million people suffer from depression worldwide1. The enormous treatment gap calls for innovative solutions in the delivery of mental-health care. In low-resource settings, a “task-shifting” approach may be beneficial in using human resources more efficiently2. Task shifting is the strategy of delegating care tasks to health workers who have fewer qualifications and shorter training than mental healthcare experts (e.g., psychiatrists, clinical psychologists or nurses)3.
Nevertheless, relatively little is known about individual patient differences in the effects of task shifted psychotherapeutic interventions for depression. Individual Patient Data (IPD) meta-analyses synthesize raw datasets of trials to provide cutting-edge evidence of outcomes that cannot be examined by conventional meta-analytic approaches4.
In the present study, we aim at conducting an individual patient data meta-analysis to develop a precision treatment rule for task-shifted psychotherapy for adult depression relative to control conditions based on secondary analysis of randomised controlled trials (RCTs) in low- and middle-income countries (LMICs).
Keywords: Social and Behavioral Sciences; Individual Patient data Meta-analysis; Low and Middle Income Countries; Psychotherapy; Task-sharing; task-shifting